2005
DOI: 10.1097/01.pec.0000159050.19188.23
|View full text |Cite
|
Sign up to set email alerts
|

Epidemiology of Pediatric Emergency Department Use at an Urban Medical Center

Abstract: Nearly half of pediatric emergency visits are for nonurgent care. Racial disparities in use of the ED for nonurgent care may be related to patient's proximity to the hospital. Patterns of use are stable across the 3 years. Further study is needed to identify mutable factors in emergency care use.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
31
0
3

Year Published

2006
2006
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 47 publications
(35 citation statements)
references
References 16 publications
1
31
0
3
Order By: Relevance
“…8,10,13,14,21 Nevertheless, the literature suggests that frequent use of the ED for nonemergent care is not the primary cause of overcrowding. 26,27 We noted a relatively high admission rate on the second visit. DePiero et al 11 looked at children admitted on the second visit to a PED and found that 90% had an appropriate ED evaluation, and admission was for progression of illness ( Figure 6).…”
Section: Discussionmentioning
confidence: 94%
“…8,10,13,14,21 Nevertheless, the literature suggests that frequent use of the ED for nonemergent care is not the primary cause of overcrowding. 26,27 We noted a relatively high admission rate on the second visit. DePiero et al 11 looked at children admitted on the second visit to a PED and found that 90% had an appropriate ED evaluation, and admission was for progression of illness ( Figure 6).…”
Section: Discussionmentioning
confidence: 94%
“…14,15 However, these studies may be affected by different biases, including spectrum bias, as under-represented minorities are more likely to identify the ED as their usual source of health care 16–19 and use the ED for nonurgent care. 20 Therefore, among other reasons, these differences may be more of a reflection of racial and ethnic differences in ED use rather than ED management, as minorities may be more likely to present to the ED for nonsurgical or less intense causes of abdominal pain. 21 Appendicitis is the most common surgical cause of abdominal pain in the ED and the provision of analgesia to patients with appendicitis is now accepted and encouraged.…”
mentioning
confidence: 99%
“…[1][2][3] This leads to overcrowded waiting rooms and long waiting times. As a consequence, patients needing care urgently may not be treated in time, whereas patients with non-urgent problems may unnecessarily receive expensive emergency care.…”
mentioning
confidence: 99%